2022
DOI: 10.1080/09637486.2022.2104227
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and physical activity in Down syndrome pediatric subjects: the DONUT STUDY

Abstract: investigate to what extent the choices of the subject are close to the correct Mediterranean diet; a +1 score is assigned in case of a positive answer and a 0 score in case of a negative answer. Questions 6, 12, 14, 16 investigate how much the subject's habits deviate from the Mediterranean diet; a score of -1 is given in case of a positive answer and a score of 0 in case of a negative answer. After scoring each response, the points are added together to calculate the total score, and then this is interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Nutritional and physical activity guidelines can be applied to the general and pediatric populations with DS. Despite potential challenges, individuals with DS can adopt a proper diet and approach physical activity similarly to children without DS [46]. Hence, these strategies also benefit children's health and well-being for individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional and physical activity guidelines can be applied to the general and pediatric populations with DS. Despite potential challenges, individuals with DS can adopt a proper diet and approach physical activity similarly to children without DS [46]. Hence, these strategies also benefit children's health and well-being for individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…With age, it becomes more and more difficult to persuade teenagers to play sports regularly. However, the DONUT STUDY showed that, despite potential difficulties in the pursuit of a correct diet and inadequate approach to physical activity, children with DS could achieve results that are substantially the same as those of non-DS children [ 90 ]. Moreover, some children and adolescents with DS are limited by reduced respiratory efficiency and congenital heart diseases [ 81 ].…”
Section: Down Syndromementioning
confidence: 99%